2018
DOI: 10.1007/s00266-018-1085-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Assisted Liposuction (LAL) Versus Traditional Liposuction: Systematic Review

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
0
19
0
5
Order By: Relevance
“…31 In contrast, nonthermal lipid harvesting techniques fail to stimulate adipocyte collagen deposition and to firm sagging skin and its underlying structures. 12,32,33 LAL in general, and 1470 nm LAL, in particular, achieves favorable and durable skin retraction outcomes, broadening treatment site criteria to include any region with even modest degrees of skin laxity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In contrast, nonthermal lipid harvesting techniques fail to stimulate adipocyte collagen deposition and to firm sagging skin and its underlying structures. 12,32,33 LAL in general, and 1470 nm LAL, in particular, achieves favorable and durable skin retraction outcomes, broadening treatment site criteria to include any region with even modest degrees of skin laxity.…”
Section: Discussionmentioning
confidence: 99%
“…A wavelength‐dependent dermal response was demonstrated in several works, where low‐energy lasers generally had a more extensive skin tightening effect as compared with higher energy lasers, possibly related to the end temperatures or to the targeted subdermal chromophores 31 . In contrast, non‐thermal lipid harvesting techniques fail to stimulate adipocyte collagen deposition and to firm sagging skin and its underlying structures 12,32,33 . LAL in general, and 1470 nm LAL, in particular, achieves favorable and durable skin retraction outcomes, broadening treatment site criteria to include any region with even modest degrees of skin laxity.…”
Section: Discussionmentioning
confidence: 99%
“…The One STEP laser technique for liposuction was recently developed and used in plastic surgery, the fat graft obtained with this Volume 5 | Issue 1 novel technique is homogenous, without lumps, and has high concentration of viable stimulated aspirate adipose-derived stem cells and a high number of viable adipocytes [20]. Therefore, there is a lack of studies regarding this subject, especially comparisons between the outcomes of laser-assisted liposuction and conventional liposuction [21].…”
Section: Discussionmentioning
confidence: 99%
“…Though theoretically laser-assisted liposuction was found to be advantageous from the surgeons' point of view and the cosmetic outcome was better, most studies were found to have a biased conclusion. 37 The technology-driven devices often have industry backing making their outcomes biased. The most recent innovation in the field of nonsurgical lipolysis is Cryolipolysis.…”
Section: Assisted Liposuctionmentioning
confidence: 99%